Столица полей: стихотворения и поэма / Юрий Лощиц - Лощиц Юрий Михайлович (Советский писатель, 1990)
Экземпляры: КХ (20111128) / Инвентарный номер: 957857 / Цена: 0.45 / Сис.шифр: Р2 / Авт.знак: Л 81 / ГРНТИ: 17 / ББК: 84(2)